Peer and Friend Influences on Children's Eating. Issue 1 (24th July 2013) - Houldcroft, Laura; Haycraft, Emma; Farrow, Claire
Abstract Peers and friends are perceived as important role models for the formation of children's attitudes and behaviours. A wealth of research has aimed to establish the contribution of peers and friends to children's developing eating behaviours, and their attitudes towards eating. This review describes and evaluates such research. Experimental research examining peer modelling of food consumption and liking is reviewed, and several individual child factors that are suggested to make children more or less receptive to peer and friend influences are discussed. The influence of children's perceptions of their peers' and friends' eating behaviours upon their own eating practices is also explored. The benefits of future longitudinal research to improve understanding of peer and friend influences on children's eating are emphasized.